Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Informatika Di SMK - Syakuro, Abdu Abdan; Astuti, Cindy Cahyaning; Wiguna, Akbar (EDUTIC, 2024)
The learning process has an influence in achieving significant learning outcomes, including learning media, learning motivation and learning models, learning models are a learning plan that will take place which contains a learning design. The learning model refers to the learning method that will be used, including learning objectives, learning stages, learning environment, and classroom management. To improve learning outcomes, it is necessary to improve the model that influences learning outcomes, where the learning model greatly influences learning outcomes, this can improve learning outcomes significantly. In the learning that took place at the Antarctic 1 Sidoarjo school, there were students who were hyperactive and less conducive due to several things including students who did not like to be restrained and needed more attention to be able to implement conducive learning, in overcoming this problem, the researcher chose a guided inquiry learning model to improve learning outcomes, this is because this learning model is more fun with learning that is packaged in a question, which is able to improve students' understanding by asking questions to satisfy their curiosity, in implementing this model the researcher used the One Group Pretest Posttest research design, by giving the same treatment to a population with two meetings, starting with giving recognition to the Pretest and ending with the Posttest. Then the data is processed to see the effect of giving treatment in the population. Hypothesis testing using the paired t-test formula (T-Paired) produces a decision that is rejected H0, the calculation of the influence with the eta square test from the table of criteria results shows a large influence. It can be concluded that there is an influence on student learning outcomes in informatics subjects using the guided inquiry learning model.